حديث "حق المعبود وحق العباد": دراسة عقدية - القرعاوي، علي بن عبدالرحمن بن سليمان (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بدمنهور, 2020)
حديث معاذ بن جبل في بيان الحقوق من الأحاديث المتفق على صحتها وهو من أعظم الأحاديث في بيان حق الله تعالى على عباده. يتجلى في هذا الحديث منهج النبي عليه الصلاة ولسلام في تقرير مسائل العقيدة؛ حيث سلك نبينا محمد صلى الله عليه وسلم أساليب ومواقف تربوية؛ لتعميق العقيدة في نفوس الصحابة رضون الله عليهم، وكان منهجا مبتكرا؛ مبتدأ بالإرادة الفردية، ومعرفة الأسباب مع توفر الوسائل؛ من الحوار والتجديد في إلقاء الأسئلة، وإثارة انتباه المتعلم من أصحابه. في الحديث حسن أدب صحابة النبي صلى الله عليه وسلم معه حيث لا يسبقونه بالقول ويصغون إلى تعاليمه باهتمام شديد. أعظم حق لله تعالى على عباده: أن يعبدوه ولا يشركوا به شيئا. العبادة والعبودية لله اسم جامع لكل ما يحبه الله ويرضاه من العقائد، وأعمال القلوب، وأعمال الجوارح؛ فكل ما يقرب إلى الله من الأفعال، والتروك فهو عبادة. توحيد العبادة هو: إخلاص الدين لله، وإفراد الله بالعبادة، وصرف جميع أنواع العبادة له سبحانه وتعالى. للعبادة شروط وهي الإخلاص والمتابعة، ولها أركان هي: الخوف والرجاء والحب. وحق العباد على الله ألا يعذب من لا يشرك به شيئا، وهذا الحق أوجبه الله على نفسه تفضلا على عباده، فهو سبحانه كتب على نفسه الرحمة، وحرم الظلم على نفسه، لا أن العبد نفسه مستحق على الله شيئا كما يكون للمخلوق على المخلوق، فإن الله هو المنعم على العباد بكل خير فهو الخالق لهم وهو المرسل إليهم الرسل، وهو الميسر لهم الإيمان والعمل الصالح. من مات وهو لا يشرك بالله شيئا داخل الجنة إما ابتداء أو انتهاء لكنه لا يخلد في النار.
The hadith of Muadh ibn Jabal regarding the description of rights is one of the hadiths agreed to be authentic, and it is one of the greatest hadiths in explaining the truth of God Almighty over His servants. This hadith reflects the approach of the Prophet, peace and blessings be upon him, in determining matters of faith. Where our Prophet Muhammad, may God bless him and grant him peace, followed educational methods and positions; To deepen belief in the hearts of the Companions, may God be pleased with them, and it was an innovative approach; Beginning with the individual will, knowing the causes and providing the means; From dialogue and innovation to questioning, and to arouse the learner's attention from his companions . In the hadith, the good manners of the companions of the Prophet, may God’s prayers and peace be upon him, were with him. They do not precede him by saying and listen to his teachings with great interest. The greatest right of God Almighty over His servants: to worship Him and not associate anything with Him. Worship and servitude to God is a name that collects all that God loves and is satisfied with from beliefs, actions of hearts, and deeds of prey. So all that is close to God from actions, and neglect is worship. That is why the neglector of disobedience to God was a devoted worshiper close to his Lord by that Monotheism of worship is: devotion of religion to God, singling out God to worship, and dispensing all kinds of worship to Him Almighty, so it is not permissible for him to join him in his worship, neither a close king nor a messenger prophet, and anything below them is a more appropriate matter. Worship has conditions, which are sincerity and follow-up, and it has pillars: fear, hope, and love . And the right of the servants over God not to torment the one who does not associate with him anything, and this right that God has enjoined upon himself in preference to his servants, for he, the Glory be to Him, wrote mercy on himself, and forbade injustice against himself, not that the servant himself deserves something from God as it is for a creature over a creature, for God He is the one who bestows the servants with all good, for he is their creator, he is the messengers to whom he is sent, and he is the facilitator for them in faith and good deeds. Whoever dies without associating anything with God will enter Heaven, either beginning or ending, but he will not abide in Hell .
Keywords: الحديث الشريف -- العقيدة الإسلامية -- العبادة